Relationship Between ANC Visits, History Of Illness, And Distance Of Pregnancy With Chronic Energy Deficiency (CED) Events In Trimester Iii Pregnant Women At Cahya Maju Puskesmas, Lempuing District, Oki Regency In 2021 - Dhany Nuzulla Synta; Ahmad Arif; Putu Lusita Nati Indriani; Helni Anggraini; Dewi Ciselia (Institute of Computer Science (IOCS), 2022)
Chronic Energy Deficiency (CED) refers to a state where mothers suffer from the chronic calorie and protein deficiency (malnutrition) leading to health problems in women of childbearing age (WCA) and in pregnant women. Factors that affect CED include direct, indirect and biological factors. This study aims to determine the correlation of ANC visits, disease history and pregnancy distance simultaneously with the occurrence of CED in third trimester pregnant women at the Cahya Maju Health Center, Lemembu Sub-district, OKI Regency in 2021. The research design used in this study was an analytical survey with a cross sectional approach. The population in this study were all pregnant women in the third trimester with a total number of 93 people at the Cahya Maju Health Center, Lemembu Sub-district, OKI Regency from January to December 2021. The sampling technique used was Total Sampling with a total of 93 people. Based on the results of the study using the Chi-square statistical test, it could be figured out that there was a significant correlation of ANC visits and the occurrence of CED in third trimester pregnant women with p value = 0.031. Also, it was found that there was a significant correlation of disease history and the occurrence of CED in third trimester pregnant women with p value of = 0.000, and there was a significant correlation of the pregnancy distance to the occurrence of CED in third trimester pregnant women with the p value = 0.028. Thus, it can be concluded that there is a relationship between ANC visits, disease history and pregnancy distance partially or simultaneously with the occurrence of CED third trimester pregnant women at the Cahya Maju Health Center,